(3cJGH aj efGbH Ydi QVi Gddg Yfgs ((3eMeO Hf ESeGYjd Hf jMji Hf GdMSjf s)
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai CNHQfG HgGA GdOjf Ydi Hf CMeO GdCchYCeG HYO aEf Chdi eG ONQg hcSHg GdYHGO eG jCedhf Hg GdfLGI jhe GdeYGO s
(3BNQgG (B:s
(3bGd bGd QShd Gddg (B( (3U(B) (3dYdi (B: (3CfJ efi HefRdI gGQhf ef ehSi hNdag ai Cgdg Yf bJGOg Yf SYjO CHj GdeSj Yf SYO Hf CHj hbGU bGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ ahGJMgG HGdSejcs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs